2019
DOI: 10.32593/jstmu/vol2.iss1.27
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression, physical activity levels and general psychological health among physical therapy students of Rawalpindi and Islamabad.

Abstract: Objective: To determine the association of depression, physical activity (PA) levels and general psychological health among physical therapy students of Rawalpindi and Islamabad. Methodology: This was a cross-sectional study conducted among students of physiotherapy department at Rawalpindi and Islamabad Institutions, from August 2015 to January 2016. Five hundred students were recruited using non-probability convenient sampling. The data was collected through a questionnaire that comprised of demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…A high percentage of the undergraduate students (45.5%) who participated in this study suffer from some type of mental disorder (GHQ12 score ≥ 4), with the incidence being significantly higher in females (48.4%) than in males (38.1%). These results are in line with the research carried out by Qureshi et al [52], who found in a sample of undergraduate students from Pakistan that a large number of the students (42.6%) had mild depression. Likewise, Üner et al [53], in an investigation of undergraduate students from Turkey, showed that 56.8% of students had a GHQ12 score ≥ 4.…”
Section: Discussionsupporting
confidence: 92%
“…A high percentage of the undergraduate students (45.5%) who participated in this study suffer from some type of mental disorder (GHQ12 score ≥ 4), with the incidence being significantly higher in females (48.4%) than in males (38.1%). These results are in line with the research carried out by Qureshi et al [52], who found in a sample of undergraduate students from Pakistan that a large number of the students (42.6%) had mild depression. Likewise, Üner et al [53], in an investigation of undergraduate students from Turkey, showed that 56.8% of students had a GHQ12 score ≥ 4.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that participants who put more hours of physical activity into their daily routines had better mental health and were less likely to develop distress and anxiety symptoms. Many studies have reported that performing daily exercise can have positive impacts on anxiety and distress symptoms – see, for example, Qui et al, Peyman et al, Zhang et al, [ 38 – 40 ]. Due to sedentary lifestyles during the COVID-19 pandemic, it has been observed that people tended to give less attention to their physical health than in normal circumstances [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, we focused on family size, and the possible explanation for family size to reverse the effect of the ripple effect vs. typhoon eye effect might be due to socio-economic burden on the families due to lockdown in the country. As studies have shown that nancial constraints or economic hardships not only increased behavioral problems but also damaged the physical and mental health status of individuals and their families [32]. Thus, our ndings identify family size as a critical contingency factor in the prediction of typhoon eye effect and ripple effect.…”
Section: Discussionmentioning
confidence: 49%